Determinants of Gen Z tourists’ intention to participate in local food tours: A case study of Hai Phong, Vietnam - PHUONG, Nguyen Van; LINH, Pham Thi; HUONG, Hoang Thi; QUYNH, Pham Ngoc Huong (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to identify and evaluate the factors influencing Gen Z tourists’ intention to participate in food tour experiences in Hai Phong, Vietnam, thereby proposing solutions to enhance experience quality and promote sustainable culinary tourism development. The study is grounded in the Theory of Planned Behavior (TPB), the Theory of Reasoned Action (TRA), the 4E model, and insights from previous studies to formulate hypotheses regarding factors affecting Gen Z tourists’ intention to engage in food tours. Key factors identified include convenience, trust, price, food safety and hygiene, food quality, service quality, and social media influence. A survey was conducted with 328 Gen Z tourists in Hai Phong, and data were analyzed using statistical methods to examine the relationship between these factors and the intention to participate in food tours. The results reveal that price has the greatest impact on Gen Z’s intention to participate in local food tours, while advertising exerts the least influence. Additionally, food safety and hygiene challenges, convenience, and service quality are identified as key barriers to developing culinary tourism in Hai Phong. The study contributes to understanding the determinants of Gen Z tourists’ intention to participate in food tours and offers insights into the specific challenges facing culinary tourism development in Hai Phong. The findings provide useful recommendations for businesses, restaurants, and tourism managers to enhance the quality of food tour experiences. Strategies include improving food safety and hygiene practices, ensuring service quality, and offering affordable and convenient options. Additionally, leveraging social media to build trust and promote culinary tourism is essential for sustainable tourism development and economic growth in Hai Phong, Vietnam.